2004
DOI: 10.1016/j.marchem.2004.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Total mercury in the water column near the shelf edge of the European continental margin

Abstract: The purpose of this paper is to investigate the distribution and the relative importance of processes that affect mercury distribution in the water column at the shelf edge of the Celtic Sea, on the western European continental margin. The water column, down to 4500 m, was sampled during two cruises, one in winter 1994 and the other in June 1995, on eight stations. Total mercury concentrations ranged from 0.29 to 9.37 pM with the extreme values in the first 200 m. The highly variable concentrations in the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 34 publications
3
32
0
1
Order By: Relevance
“…Given the small volume of inflow (Table 2), the best estimate Pacific contribution to the Arctic is 3.9 t year −1 , which is an order of magnitude smaller than the North Atlantic contribution of 44.2 t year −1 based on a mean seawater Hg concentration of 0.40 ng L −1 . [78] For calculation purposes, we have assumed outflows through the Canadian Archipelago and Fram Strait were equivalent to the inflows through the Bering Strait and the Barents Sea, respectively, plus a small additional outflow (3090 km 3 year −1 , divided between the two outlets) to account for freshwater inflows to the ocean. Best estimate concentrations of 0.50 and 0.48 ng L −1 , respectively (Table 2), give Hg effluxes of 13.6 and 53.9 t year −1 .…”
Section: Oceansmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the small volume of inflow (Table 2), the best estimate Pacific contribution to the Arctic is 3.9 t year −1 , which is an order of magnitude smaller than the North Atlantic contribution of 44.2 t year −1 based on a mean seawater Hg concentration of 0.40 ng L −1 . [78] For calculation purposes, we have assumed outflows through the Canadian Archipelago and Fram Strait were equivalent to the inflows through the Bering Strait and the Barents Sea, respectively, plus a small additional outflow (3090 km 3 year −1 , divided between the two outlets) to account for freshwater inflows to the ocean. Best estimate concentrations of 0.50 and 0.48 ng L −1 , respectively (Table 2), give Hg effluxes of 13.6 and 53.9 t year −1 .…”
Section: Oceansmentioning
confidence: 99%
“…Faroes-UK-Scandinavia Best estimate from Cossa et al [78] Archipelago outflow (including waters of the Archipelago and Davis Strait) Resolute Passage, Ellesmere Is. St. Louis et al [54] MeHg only (30-45% of total Hg)…”
Section: 84mentioning
confidence: 99%
“…A growing body of evidence suggests that Hg is strongly associated with organic matter in the modern ocean. Profiles of seawater Hg exhibit minimum concentrations in the photic zone, with stable or slightly increasing concentrations with depth (Cossa et al, 1997;Ferrara et al, 2003;Cossa et al, 2004;Laurier et al, 2004;Kotnik et al, 2007). Photochemical and biological reduction of Hg(II) with subsequent evasion of Hg(0) likely contribute to the photic zone Hg concentration minima (Cossa et al, 1997;Kotnik et al, 2007).…”
Section: Trace Metal Enrichments In Sapropel Sedimentsmentioning
confidence: 99%
“…In relation to Cd and Hg sources, could come from Orinoco river discharge, which has high levels of these metals (Laya, 1992), and they are being transported along the east coast of Venezuela by the prevailing marine currents in the area (Rojas et al, 2002). Furthermore, these are metals which have biogeochemical behavior similar the ones of nutrients; consequently, upwelling waters may be enriched with some metals, constituting the main source of Hg and Cd to the coastal areas (Cossa et al, 2004, Valdés et al, 2006. On the other hand, laboratory experiments and field evidences have demonstrated that accumulate Zn and Cu in otoliths is predominantly via dietary exposure rather than through waterborne exposure (Campana 1999, Milton et al, 2000, Ranaldi and Gagnon, 2008b.…”
Section: Resultsmentioning
confidence: 99%